The role of geographical mobility and ‘escalator regions’ in intergenerational social mobility: Life course analysis linking the Scottish Mental Survey 1947 and Scottish Longitudinal Study data - Adair, Lynne; Deary, Ian; Feng, Zhiqiang; Dibben, Chris (International Journal of Population Data Science, 2025)
Objective The escalator region hypothesis proposes that regions which offer positive job opportunities may enhance occupational mobility. We explored whether intergenerational mobility might also be enhanced by a move to an escalator region and whether this may be due to the place itself to the particular characteristics of spatially-mobile individuals. Methods We used data from the Scottish Mental Survey 1947 (a 1936 birth cohort with age 11 cognitive ability test scores) and 1939 Register (a national register which records parental occupation and location) linked to the Scottish Longitudinal Study (a 5.3% sample of the Scottish population created from census data, which we used to obtain midlife occupation, geographical location and educational qualifications in 1991) to investigate if major Scottish urban centres act as escalator regions. We looked at mobility between five geographical regions in Scotland to explore the patterns of intergenerational social and geographical mobility in this cohort, and their characteristics. Results We found that childhood cognitive ability and achieved education level were significantly associated with intergenerational upward mobility from childhood to middle age. Spatially-mobile people had higher social status in adulthood than non-movers. Scotland’s capital city, Edinburgh, does appear to be an escalator region, as those who moved there were more likely to be upwardly mobile than those who remained there or moved elsewhere in Scotland. Movers to an escalator region (Edinburgh) were more likely to be in a high adult social status even when parental social status and individual characteristics were adjusted for. Conclusion Findings from this study suggest that geographical mobility can lead to greater intergenerational social mobility, and that both person and place are important. However, a move to an escalator region appears to enhance social mobility beyond individual characteristics.